The set of test tasks assessing special physical fitness of 17-year-old soccer players - Szwarc, A.; Dolanski, B.; Lipinska, P. (Baltic Journal of Health and Physical Activity, 2015)
Background: The objective of the research was to work out the set of test tasks assessing special physical fitness of 17-year-old soccer players. Material/Methods: At first, on the basis of the analysis of the said issue in literature and the authors` own coaching experience, 13 test tasks were selected. Next, reliability and accuracy of the chosen test tasks were examined on the group of 16 athletes from the Centre of Sports training for youth in Gdansk. The reliability was assessed by the test-re-test method and the accuracy according to a criterion of internal accuracy tests. Except for one task, all efficiency tests met scientific requirements for motor tests. Finally, with the use of statistical analysis (linear regression equation, Hellwig`s algorithm of the optimal choice of explaining variables), four tests implementing most information for the assessment of game-play were chosen. Results: A four-task set of tests assessing selected components of physical fitness reflected 86.7% of the game-play of young competitors. Conclusions: Results of special physical fitness tests should be treated as important information about young athletes` special physical efficiency, closely interdependent with the effectiveness of their activity in a classified game-play, but only when the tests themselves have previously been scientifically proved. The optimal set of tests describing in 86.7% the efficiency of activity of 17-year--old competitors in game-play should contain the following efficiency tests: "envelope" dribbling, 30m run, passing and trapping the ball with a sole of the foot against a small bench from a 3-meter-distance and kicking the ball for distance. Results of special physical fitness tests should be treated as important information about young athletes` special physical efficiency, closely interdependent with the effectiveness of their activity in a classified game-play, but only when the tests themselves have previously been scientifically proved.